PENGARUH WORK ENVIRONMENT DAN SELF REGULATION TERHADAP KEPUASAN KERJA SERTA IMPLIKASI PADA KINERJA PEGAWAI NON ASN DI KELURAHAN SE KECAMATAN CURUG KOTA SERANG - Sutihat, Sutihat; Mukhlis, Ahmad; Permana, Angrian (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This research was conducted on non-Asn employees in Curug District with the aim of knowing and analyzing the influence of the work environment on employee performance, self-regulation on employee performance, job satisfaction on employee performance, work environment on job satisfaction, self-regulation on employee job satisfaction, work environment on employee performance through job satisfaction and self-regulation on employee performance through job satisfaction. This research uses a quantitative method with a correlational design with a total population of 58 non-ASN employees in Curug District with sample determination using a quota sampling technique, namely the entire population is sampled so that the total sample used is 58 non-ASN employees. The analysis method in this research uses regression analysis with the SmartPls statistical tool. The research results obtained from seven hypotheses, three hypotheses were rejected and four hypotheses were accepted, the conclusion of this research is that work environment has a significant effect on employee performance and job satisfaction, self-regulation has no effect on employee performance but has a significant effect on job satisfaction, work environment has no effect on performance through job satisfaction and self-regulation has no effect on performance through job satisfaction